Pollution impact on recent mollusks along the Mediterranean coast between Abu Traba and Al Kuwifia, NE Libya - Bago, A. M.; M. Muftah, Ahmed; R. Shaltami, Osama; S. Al Faitouri, Mohamed; A. Elsalini, Osama (Libyan Journal of Science &Technology, 2022)
The current study assessed the levels of pollution on recent mollusks along the Mediterranean coast from Abu Traba to Al Kuwifia, Northeast Libya. Twenty-five molluskan species have been documented in total. However, only thirteen taxa were chemically analyzed in this study. The chemical analysis showed that the Cerastoderma glacum and Venus sp. are good accumulators for Zinc (Zn), Lead (Pb) and Thorium (Th), while Cerithium sp. A and Cerithium sp. B are fine collectors for Uranium (U). Most of the analyzed metals have Enrichment Factor (EF)>2 suggesting that they are mainly of anthropogenic origin. We recommend treating the pollution levels of Lead (Pb), Arsenic (As) and Selenium (Se) in different localities of the study area, especially in Abu Traba and Al Kuwifia localities.